PENGARUH MEDIA SOSIAL TERHADAP PRESTASI BELAJAR SISIWA PADA MATA PELAJARAN FIQIH DI MADRASAH TSANAWIYAH NEGERI 2 KOTA MALANG - Faizatul Khoiriyyah; M. Ilyas Thohari; Ibnu Jazari (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the problem of the influence of social media usage on student learning achievement in Fiqih subjects at Madrasah Tsanawiyah Negeri 2 Malang city. The problem face is that presence of social media increasingly makes students forget about their obligation to study. This study used is a quantitative method and the type of research used is causal research which is to find out the causal relationship. Data collection is done by observation, interviews, questionnaires and documentation. The data analysis technique used is descriptive analysis and statistical analysis which include validity test, reliability test and hypothesis test. Where the formula used for hyphothesis testing is simple linear regression analysis. The result of this study are that students use social media so well, there is no significant influence on student learning achievement, especially of Fiqih subject.